Application of a Body Map Tool to Enhance Discussion of Sexual Behavior in Women in South Africa, Uganda, and Zimbabwe. Issue 2 (May 2021) - Naidoo, Sarita; Duby, Zoe; Hartmann, Miriam; Musara, Petina; Etima, Juliane; Woeber, Kubashni; Mensch, Barbara S.; der Straten, Ariane van; Montgomery, Elizabeth T.
Body mapping methods are used in sexual and reproductive health studies to encourage candid discussion of sex and sexuality, pleasure and pain, sickness and health, and to understand individuals' perceptions of their bodies. VOICE-D, a qualitative follow-up study to the VOICE trial, developed and used a body map tool in the context of individual in-depth interviews with women in South Africa, Uganda, and Zimbabwe. The tool showed the outline of a nude female figure from the front and back perspective. We asked women to identify, label, and discuss genitalia and other body parts associated with sexual behaviors, pain, and pleasure. Respondents could indicate body parts without having to verbalize potentially embarrassing anatomical terms, enabling interviewers to clarify ambiguous terminology that may have otherwise been open to misinterpretation. Body maps provided women with a non-intimidating way of discussing and disclosing their sexual practices, and minimized miscommunication of anatomical and behavioral terminology.